2021
DOI: 10.1101/2021.11.01.466853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil microbes mediate the effects of environmental variability on plant invasion

Abstract: Many studies indicate that increases in resource variability promote plant invasion. However, it remains unknown to what extent these effects might indirectly be mediated by other organisms. To test this, we grew eight alien species in pot-mesocosms with five different native communities under eight combinations of two nutrient-availability, two nutrient-fluctuation and two soil-microbe treatments. We found that when plants grew in sterilized soil, nutrient fluctuation promoted the dominance of alien plants un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
(37 reference statements)
2
10
0
1
Order By: Relevance
“…In other words, nutrient fluctuations affect alien dominance both directly and indirectly through herbivore influence. A similar mediation effect was observed with soil pathogenic fungi (Zhang et al, 2021). These two studies suggest that higher trophic levels do mediate alien invasion success under nutrient fluctuations.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In other words, nutrient fluctuations affect alien dominance both directly and indirectly through herbivore influence. A similar mediation effect was observed with soil pathogenic fungi (Zhang et al, 2021). These two studies suggest that higher trophic levels do mediate alien invasion success under nutrient fluctuations.…”
Section: Introductionsupporting
confidence: 78%
“…Recent studies indicate that nutrient fluctuation may affect alien plant invasion both directly and indirectly through higher trophic levels (Gao et al, 2021; Li et al, 2022; Zhang et al, 2021). Our experimental evidence indeed supports this hypothesis, demonstrating that nitrogen fluctuation could enhance the dominance of the alien species in native communities, especially when AMF inoculation was absent.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent meta-analysis has shown that exotic plants are more capable of utilizing added nitrogen than native plants (Liu et al 2017). However, there are also studies that do not support this hypothesis, namely that increased nutrient availability suppresses the invasion of exotic plants (Li et al 2022b; Zhang et al 2021b). Therefore, more research is needed to test the impact of resource availability and uncover the causes of the many ways that invasive plants react to resource changes, which can have an impact on outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for the mixed findings could be that most studies did not consider interactions of the plants with other organisms (Copeland et al, 2016; Liu et al, 2017; Pintó‐Marijuan et al, 2017; Valliere et al, 2019). Recent studies found evidence that other trophic levels could indirectly mediate the responses of alien plants to nutrient availability and variation therein (Li et al, 2022; Zhang et al, 2021). However, whether drought can affect alien plant invasion via other trophic levels remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%